The effects of oral vaccination of Streptococcus agalactiae on stimulating gut-associated lymphoid tissues (GALTs) in tilapia (Oreochromis spp.) - Nawi, Mohd Firdaus; Omar, Noraini; Mohd Yusoff, Sabri; Abdullah, Siti Zahrah; Saad, Mohd Zamri; H., Latifah (Universiti Putra Malaysia Press, 2011)
Vaccination of fish by intraperitoneal (i.p.) injection and bath immersion against bacterial infections has been proven to be a commercial success. However, those routes of vaccination are not economical in practice due to several reasons such as high labour cost, highly time consuming, and causing stress to the fish. Meanwhile, oral vaccination is considered as the best route to vaccinate the fish due to less stress to the fish, ability to treat large batch at one time, and easy and practical to administer booster vaccination. In this study, effect of oral vaccination with various regimes in stimulating gut-associated lymphoid tissues (GALTs) against Streptococcus agalactiae infection was observed. In this vaccination experiments, four groups of fish with four replicates consisting of 15 tilapias each were used; four groups per treatment received antigen incorporated vaccine in different regimes. Group 1 was fed with vaccine once per week, Group 2 was fed three consecutive days per week, and Group 3 was fed five consecutive days per week, while Group 4 (control) was fed with standard commercial feed. Booster dose was administered at day-14 after the first administration, and humanely killed at day-28 post-booster vaccination. Ten fish from each group were collected for gut sampling and subjected for histological analysis using Olympus FIVE Image Analyzer. Aggregations of GALTs were observed in lamina propria of the gut. The sizes of GALTs were measured and the numbers of lymphoid cells were also counted. The diameter of GALTs showed no significant (p>0.05) difference between Groups 1 to Group 2 and Group 2 to Group 3, but a significant difference (p<0.05) was observed between Groups 1 and 3. In terms of the numbers of lymphoid cells, no significant differences (p>0.05) were found between Group 1 to Group 2 and Group 2 to Group 3; however, a significant difference (p<0.05) was observed between Groups 1 and Group 3. As a conclusion, the frequencies of administration play a role in stimulating the size of GALT which is correlated with the number of aggregated lymphoid cells in the gastrointestinal tract of tilapia.